2009
DOI: 10.1007/s12194-008-0046-x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging simulations of an “OpenPET” geometry with shifting detector rings

Abstract: We have proposed a new "OpenPET" geometry consisting of two detector rings of axial length W each separated by a gap G. For obtaining an axially continuous field of view (FOV) of 2W + G, the maximum limit for G must be W. However, two valleys of sensitivity appear on both sides of the gap. Setting a more limited range for the gap as G < W, which is desirable for filling in the sensitivity valleys, results in not only a shortened gap, but also a shortened axial FOV. In this paper, we propose an alternative meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
(17 reference statements)
0
6
0
Order By: Relevance
“…The gap imaging would be affected by loss of low-frequency components because the gap, where direct LORs do not exist, is imaged only from the oblique LORs. However our previous simulation results have shown that the OpenPET imaging is acceptable except for extreme situations such as the Defrise phantom (Yamaya et al 2008a(Yamaya et al , 2009b. Therefore we think that there might be an effect to compensate for the frequency truncation in iterative image reconstruction.…”
Section: Phantom Experimentsmentioning
confidence: 93%
See 1 more Smart Citation
“…The gap imaging would be affected by loss of low-frequency components because the gap, where direct LORs do not exist, is imaged only from the oblique LORs. However our previous simulation results have shown that the OpenPET imaging is acceptable except for extreme situations such as the Defrise phantom (Yamaya et al 2008a(Yamaya et al , 2009b. Therefore we think that there might be an effect to compensate for the frequency truncation in iterative image reconstruction.…”
Section: Phantom Experimentsmentioning
confidence: 93%
“…Our previous reports have shown feasibility of OpenPET imaging through numerical simulations (Yamaya et al 2008a(Yamaya et al , 2009b(Yamaya et al , 2009c. In this paper, therefore, we develop the first small prototype to show a proof-of-concept of OpenPET imaging.…”
Section: Introductionmentioning
confidence: 98%
“…We have proposed the OpenPET geometry which can provide an accessible open space to the patient during positron emission tomography (PET) scanning (Yamaya et al 2008, 2009a, 2009b, 2011and Yoshida et al 2010. The OpenPET has mainly three types of possible applications: (1) integration of treatment and diagnosis; (2) simultaneous multimodal imaging and (3) entire-body PET with a limited number of detector rings.…”
Section: Introductionmentioning
confidence: 99%
“…We are developing an open-geometry PET scanner, OpenPET, which has axially separated detector rings and a physically opened field of view (Yamaya et al 2008, 2009a, 2009b, 2009c, 2011, Yoshida et al 2010, Tashima et al 2012a. The OpenPET geometry can reduce patient stress due to claustrophobia during PET brain imaging.…”
Section: Introductionmentioning
confidence: 99%